Dual-Branch Residual Network for Enhanced Steel Plate Fault Detection - Chen, Hao; Lu, Jiaxin (Journal of advanced computational intelligence and intelligent informatics, 2025)
Steel plate fault detection plays a crucial role in industrial manufacturing. However, the inherent complexity of steel plate fault data and the redundancy of certain features pose significant challenges for effective feature extraction. To address these challenges, we propose a dual-branch residual network model (DRNM), which utilizes a two-branch architecture. The first branch processes the original data through a convolutional neural network to capture local feature details, and the second branch leverages feature mapping to extract the spatial relationships within the data. To enhance feature extraction depth and model performance, residual networks are integrated into both branches, allowing for deeper network training and the capture of richer feature representations. The proposed dual feature extraction mechanism significantly improves the model’s representational power and fault-detection accuracy. Experimental results on a public dataset demonstrate that DRNM achieves state-of-the-art performance, with average recall and F1 score of 90.11% and 90.79%, respectively, substantially outperforming existing methods.